Dunia Melayu dan dunia Indocina - International Conference on the Malay Civilization 1989 Kuala Lumpur, Malaysia); Ismail Hussein Datuk 1932-; Lafont, Pierre-Bernard (Kuala Lumpur Dewan Bahasa dan Pustaka, Kementerian Pendidikan, Malaysia, 1995)
History of socio-cultural relations between Malay and Indochina; collection of articles.
In Malay.
Keywords: Indochina -- Relations -- Malay Peninsula -- Congresses; Malay Peninsula -- Relations -- Indochina -- Congresses; Indochina -- Civilization -- Congresses; Malay Peninsula -- Civilization -- Congresses